Understanding women's attitudes towards wife beating in Zimbabwe - Hindin Michelle J. (The World Health Organization, 2003)
OBJECTIVE: To investigate the factors associated with attitudes towards wife beating among women in partnerships in Zimbabwe in order to assist public health practitioners in preventing intimate partner violence (IPV). METHODS: A nationally representative survey of 5907 women of reproductive age (15-49 years) was conducted in Zimbabwe. Women were asked about their attitudes towards wife beating in five situations. The survey included sociodemographic characteristics, partnership characteristics, and household decision-making. FINDINGS: Over half of all women in Zimbabwe (53%) believed that wife beating was justified in at least one of the five situations. Respondents were most likely to find wife beating justified if a wife argued with her spouse (36%), neglected her children (33%), or went out without telling her spouse (30%). Among women in partnerships (n = 3077), younger age, living in rural areas, lower household wealth, schooling at a lower level than secondary, and lower occupational status were associated with women reporting that wife beating is justified. Women who reported that they make household decisions jointly with their partners were less likely to say that wife beating is justified. CONCLUSIONS: Zimbabwe has a long way to go in preventing IPV, particularly because the younger generation of women is significantly more likely to believe that wife beating is justified compared with older women. Given the current social and political climate in Zimbabwe, finding means to negotiate rather than settle conflict through violence is essential from the household level to the national level.